Lévinas, Emmanuel - Peckhaus, Volker (Enzyklopädie Philosophie und Wissenschaftstheorie, Bd. 4: Ins–Loc)

Spoken English through the centuries: Introduction - Claridge, Claudia; Mindt, Ilka (Anglistentag 2009 Klagenfurt. Proceedings)

Methoden der Korpuslinguistik: Der korpus-basierte und der korpus-geleitete Ansatz - Mindt, Ilka (Kompendium Korpuslinguistik. Eine Bestandsaufnahme aus deutsch-tschechischer Perspektive)

Hormone-based Control for Multi-modular Robotics - Hamann, Heiko; Schmickl, Thomas; Stradner, Jürgen; Crailsheim, Karl; Levi, Paul; Kernbach, Serge (Symbiotic Multi-Robot Organisms: Reliability, Adaptability, Evolution)

Page migration in dynamic networks - Bienkowski, Marcin

Collective graph exploration - Dynia, Miroslaw

Kinetic Facility Location - Degener, Bastian; Gehweiler, Joachim; Lammersen, Christiane (Algorithmica)

Literaturwissenschaft - Eke, Norbert Otto; Allkemper, Alo
4. Auflage 2014

A distributed diffusive heuristic for clustering a virtual P2P supercomputer - Gehweiler, Joachim; Meyerhenke, Henning (Proceeedings of 24th International Parallel and Distributed Processing Symposium (IPDPS, HPGC))

On Dynamic Graph Partitioning and Graph Clustering using Diffusion - Gehweiler, Joachim; Meyerhenke, Henning (Dagstuhl Seminar Proceedings 10261: Algorithm Engineering)
Load balancing is an important requirement for the efficient execu-tion of parallel numerical simulations. In particular when the simulation domainchanges over time, the mapping of computational tasks to processors needs tobe modified accordingly. State-of-the-art libraries for this problem are basedon graph repartitioning. They have a number of drawbacks, including the opti-mized metric and the difficulty of parallelizing the popular repartitioning heuris-tic Kernighan-Lin (KL).Here we further explore the very promising diffusion-based graph partitioningalgorithm DIBAP (Meyerhenke et al., JPDC 69(9):750–761, 2009) by adaptingDIBAP to the related problem of load balancing. Experiments with graph se-quences that imitate adaptive numerical simulations demonstrate the applicabilityand high quality of DIBAP for load balancing by repartitioning. Compared to thefaster state-of-the-art repartitioners PARMETIS and parallel JOSTLE, DIBAP’ssolutions have partitions with significantly fewer external edges and boundarynodes and the resulting average migration volume in the important maximumnorm is also the best in most cases.We also prove that one of DIBAP’s key components optimizes a relaxed versionof the minimum edge cut problem. Moreover, we hint at a distributed algorithmbased on ideas used in DIBAP for clustering a virtual P2P supercomputer.

Thread Migration and Checkpointing in Java - Thies, Michael; Gehweiler, Joachim

Adaptive Action Selection Mechanisms for Evolutionary Multimodular Robotics - Kernbach, Serge; Schmickl, Thomas; Hamann, Heiko; Stradner, Jürgen; Schlachter, Florian; Schwarzer, Christopher s. F.; Winfield, Alan F. T.; Matthias, Rene (Artificial Life XII (ALife XII))

Rekonstruktionen von Kontinuität zwischen 1600 und 1800: Überbrückung der durch Politik, Religion und Krieg verursachten Zäsuren - Seng, Eva- Maria (Geschichte der Rekonstruktion. Konstruktion der Geschichte. Publikation und Ausstellungskatalog, Pinakothek der Moderne)

Improved Hardness of Approximation for Stackelberg Shortest-Path Pricing - Briest, Patrick; Chalermsook, Parinya; Khanna, Sanjeev; Laekhanukit, Bundit; Nanongkai, Danupon (Workshop on Internet and Network Economics (WINE))

Algorithmische Grundlagen verteilter Speichersysteme - Meyer auf der Heide, Friedhelm; Scheideler, Christian (Informatik Spektrum)

Stadtbaukunst - Seng, Eva- Maria (Enzyklopädie der Neuzeit, Stuttgart)

Pricing Randomized Allocations - Briest, Patrick; Chawla, Shuchi; Kleinberg, Robert; Weinberg, S. Matthew (Proceedings of the Twenty-First Annual ACM-SIAM Symposium on Discrete Algorithms)

Foreword - Gavoille, Cyril; Patt-Shamir, Boaz; Scheideler, Christian (Theory of Computing Systems)

Peer-to-peer networks based on random graphs - Mahlmann, Peter

Local, distributed approximation algorithms for geometric assignment problems - Degener, Bastian

Time Complexity of Distributed Topological Self-stabilization: The Case of Graph Linearization - Gall, Dominik; Jacob, Riko; W. Richa, Andrea; Scheideler, Christian; Schmid, Stefan; Täubig, Hanjo (LATIN 2010: Theoretical Informatics, 9th Latin American Symposium, Oaxaca, Mexico, April 19-23, 2010. Proceedings)

Brief announcement: towards robust medium access in multi-hop networks - Richa, Andrea W.; Zhang, Jin; Scheideler, Christian; Schmid, Stefan (Proceedings of the 29th Annual ACM Symposium on Principles of Distributed Computing, PODC 2010, Zurich, Switzerland, July 25-28, 2010)

A Jamming-Resistant MAC Protocol for Multi-Hop Wireless Networks - Richa, Andrea W.; Scheideler, Christian; Schmid, Stefan; Zhang, Jin (Distributed Computing, 24th International Symposium, DISC 2010, Cambridge, MA, USA, September 13-15, 2010. Proceedings)

Brief Announcement: Stabilizing Consensus with the Power of Two Choices - Doerr, Benjamin; Ann Goldberg, Leslie; Minder, Lorenz; Sauerwald, Thomas; Scheideler, Christian (Distributed Computing, 24th International Symposium, DISC 2010, Cambridge, MA, USA, September 13-15, 2010. Proceedings)

Algorithms for Sensor Systems - 6th International Workshop on Algorithms for Sensor Systems, Wireless Ad Hoc Networks, and Autonomous Mobile Entities, ALGOSENSORS 2010, Bordeaux, France, July 5, 2010, Revised Selected Papers

Selected properties of a joint congestion controller for TCP connections - Savorić, Michael; Karl, Holger; Wolisz, Adam (Providing Quality of Service in Heterogeneous Environments, Proceedings of the 18th International Teletraffic Congress - ITC-18)

ANALYSING CAPACITY IMPROVEMENTS IN WIRELESS NETWORKS BY RELAYING - Karl, Holger; MENGESHA, S. (Wireless LANs and Home Networks)

ANY l-STATE ANALYTICAL SOLUTIONS OF THE KLEIN–GORDON EQUATION FOR THE WOODS–SAXON POTENTIAL - BADALOV, V. H.; AHMADOV, H. I.; BADALOV, S. V. (International Journal of Modern Physics E)
The radial part of the Klein–Gordon equation for the Woods–Saxon potential is solved. In our calculations, we have applied the Nikiforov–Uvarov method by using the Pekeris approximation to the centrifugal potential for any l-states. The exact bound state energy eigenvalues and the corresponding eigenfunctions are obtained on the various values of the quantum numbers n and l. The nonrelativistic limit of the bound state energy spectrum was also found.

Ausschau halten nach den Toten. Marcel Beyers Spurensuche im Feld der Familie - Eke, Norbert Otto (Deutsche Familienromane. Literarische Genealogien und internationaler Kontext)

„Jetzt aber Schluß!“ – Verwerfungen im Erinnerungsraum des frühen Nachkriegstheaters - Eke, Norbert Otto („Wacht auf, denn eure Träume sind schlecht!“ Literatur in den Anfangsjahren der Bundesrepublik Deutschland)

„Es ist alles wahr, was man hört.“ Die Shoah im Spiegelraum des westdeutschen Nachkriegstheaters - Eke, Norbert Otto (Die ersten Stimmen. Deutschsprachige Texte zur Shoah 1945-1963 / Les premières voix. Écrits sur la Shoah en langue allemande 1945-1963)

Der törichte Freiherr und die vernünftige Negerin. Ethnische Codierungen in Lafontaines Leben und Thaten des Freiherrn Quinctius Heymeran von Flaming - Eke, Norbert Otto (August Lafontaine (1758-1831). Ein Bestsellerautor zwischen Spätaufklärung und Romantik)

KeimZellen: Familie – Staat – Terrorismus - Eke, Norbert Otto (Familien Erzählen. Das literarische Werk John von Düffels)

„Heilig bleibt das Vaterland“. Konfigurationen des Nationalen im Historischen Drama der Restaurationszeit - Eke, Norbert Otto (Von der Spätaufklärung zur Badischen Revolution. Literarisches Leben in Baden zwischen 1800 und 1850)

Dorothee Hemme, Markus Tauschek (Hg.), Leben im Weltkulturerbe. Ethnologische Skizzen zum alltagskulturellen Umgang mit dem Prädikat UNESCO-Welterbe“, Göttingen 2008 - Seng, Eva- Maria (Bayerisches Jahrbuch für Volkskunde)

Simulating Tightly Intermeshing, Co-Rotating Twin Screw Extruders with SIGMA - Kretzschmar, Nils; Schöppner, Volker (Proceedings of the 2010 Summer Computer Simulation Conference)
A large proportion of plastics today is compounded, which means the process from refining a raw material to the processable material. For this process compounding extruders are used which mostly involve tightly intermeshing, co-rotating twin screw extruders. These extruders consist of two closely spaced screws which rotate in the same direction and convey the raw material to the screw tip. These screws are surrounded by several barrel modules which heat or cool the material. As the whole design of the machine is modularly arranged the process behavior of a twin screw extruder depends for the main part on the arrangement of the screw and the barrel elements. Until today this arrangement and process optimization is conducted by experienced engineers and with the help of trial-and-error methods. Furthermore, theoretical models are used with which the behavior of the extruder is estimated. As these models are mostly very complex they are only made available with the realization in different software projects. One of the tools is called SIGMA. Within this paper SIGMA is introduced as a software to optimize a twin screw extruder. SIGMA supports the engineer already in the early stages of the extruder arrangement.
Keywords: process optimization; polymer engineering; compounding; twin screw extruder; simulation

Brain activity in goal-directed movements in a real compared to a virtual environment using the Nintendo Wii. - Baumeister, Jochen; Reinecke, K; Cordes, M; Lerch, C; Weiss, M (Neurosci Lett)

Motor control and brain activity after prolonged exhaustive exercise: neurophysiological insights into fatigue - Baumeister, Jochen; Reinecke, K; Schubert, M; Weiss, M

Exhaustive exercise leads to changes in cortical activity and cognitive funktion - Baumeister, Jochen; Reinecke, K; Schubert, M; Weiss, M (Abstract Book - 15th Annual Congress of the European College of Sports Science)

Requirements and profile of German professional basketball - Schnittker, R; Baumeister, Jochen; Paier, D; Wilhelm, P; Weiss, M

The required number of epochs for representing brain states from spontaneous EEG - Schubert, M; Reinecke, K; Schade, J; Weiss, M; Baumeister, Jochen (ISEK 2010 - Scientific Program)

Altered brain activity after an exhaustive strength training - Reinecke, K; Schubert, M; Weiss, M; Baumeister, Jochen (Abstract Book - 15th Annual Congress of the European College of Sports Science)

The effect of visual perturbation during drop landings - Koplin, S; Kirchner, C; Koschate, J; Weiß, M; Baumeister, Jochen (Abstract Book - 15th Annual Congress of the European College of Sports Science)

Hochschulentwicklung innovativ gestalten. Das Projekt Locomotion an der Universität Paderborn

Jahrbuch Medienpädagogik 8. Medienkompetenz und Web 2.0

Flexible Resource Management for Self-X Systems: An Evaluation - Oberthür, Simon; Zaremba, Leszek; Lichte, Hermann Simon (2010 13th IEEE International Symposium on Object/Component/Service-Oriented Real-Time Distributed Computing Workshops)

Der Computer- und Videospielmarkt. Eine (medien)ökonomische Erfolgsgeschichte - Müller-Lietzkow, J.; Meister, Dorothee M. (Digitale Spielkultur)

Wissens- und Kommunikationsprozesse ethisch beratender Gremien in digitalen Gestaltungsformen - Meister, Dorothee M.; Kamin, A.-M.; Urban, D. (Medien – Wissen – Bildung. Explorationen visualisierter und kollaborativer Wissensräume)

Strategien der Professionalisierung in der Hochschuldidaktik - Urban, D.; Meister, Dorothee M. (ZFHE Zeitschrift für Hochschulentwicklung)

Lust und Schrecken medialer Gewalt. Medienpädagogische Überlegungen zum Fernsehverhalten Jugendlicher - Meister, Dorothee M.; Sander, U. (Jugend – Medien – Kultur. Medienpädagogische Konzepte und Projekte. Dieter Baacke Preis Handbuch 5)